Student perceptions of women's participation in the Legislature: Case study in Malang City government agency - Kartikasari, Ade Ana; Savero, Airell Malik; Sahida, Driya Safina; Kamandoko, Revita Anastria Adinda Putri; Wijaya, Dedhi Lugita Hadi (Jurnal Teori dan Praksis Pembelajaran IPS, 2022)
Problems regarding gender equality in Indonesia enter various domains and fields, one of which is in the realm of Legislative politics. The existence of women in the legislative sphere is often underestimated. Therefore, a survey was conducted on students' perceptions as agents of change in responding to women's participation in the legislative membership, especially in the DPRD. The case study was in the Malang City DPRD. This survey uses a descriptive qualitative method of case studies in the Malang City DPRD. Based on the results of a survey conducted by students from various faculties and different universities, they agree that the presence of women in DPRD membership will contribute to the policies formulated by legislative institutions in the future.